PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTU MEDIA KONKRIT DALAM UPAYA PENINGKATAN PROSES DAN HASIL BELAJAR MUATAN IPA TEMA7 SUBTEMA 1 KELAS 4 - Buda, Chinda Hibatul (Universitas Pendidikan Ganesha, 2018)
ABSTRACTThe research was carried out in order to improve the processes and outcomes of learning with media concrete on the charge on IPA Theme 7 subtema 1. The research was carried out on May 7-May 16, 2018 at 4th grade Student Affairs Tegalrejo 01 school year 2017/2018. This type of research using research action class. The percentage of observations of teachers has increased from 53% to cycle pre 72.5% in cycle I and 85.5% in cycle II. Students experience increased activity of pre cycle 51.67% to 71.66% in cycle I and 86.5% in cycle II. Student learning outcomes on pre cycle amounted to 11 students with a percentage of 40.74%, and not completely 16 students with percentages of 59.26%. After doing a repair on the cycle I increase that is 19 students complete with a percentage of 70.37% and 8 students not finished with a percentage of 29.63%, the result of the repair cycle I have yet to achieve the attainment of indicators i.e. 80% ketuntasan, then in to perform a repair cycle II. After the execution of the cycle II an increase in 23 students finished with a percentage of 85.19% whereas students who do not complete amounted to 14.81 percentage people with 4%. Thus improvements with the Model of Problem Based Learning with concrete media can say successful because the results of learning objectives i.e. the percentage of 80%.Keyword: Problem Based Learning, Concrete Media, processes and Outcomes of learning, science